2009
DOI: 10.1111/j.1439-0272.1981.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Doses of Alpha Chlorohydrin on the Dehydrogenases and Oxidases of Rat Epididymal Epithelium and Sperms: A Correlative Histochemical and Biochemical Study

Abstract: IntroductionAlpha chlorohydrin is a reversible antifertility agent in several species of animals (Kalla -1976). Although its use for this purpose has been rejected for human beings on account of bone marrow damage and other toxicity in rhesus monkeys (Kirton et al. -1970) but extensive and much basic work ist still going on using this research tool in order to develop its less toxic yet more active antifertility analogues. The mechanism of action of this compound continues to remain obscure. However, Mohri et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There were the highest glycolytic rates and the lower Krebs cycle rates in spermatozoa of all germ cells for its single energy source of glucose or fructose . Recently published studies showed that the activities of the glycolytic pathway, HMP pathway, and TCA cycle enzymes were estimated in caput, corpus, and cauda segments of epididymis . So the significantly increased levels of citrate, malate, and nicotinamide in the epididymis indicated reproductive energy metabolic disorders upon exposure to heat stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were the highest glycolytic rates and the lower Krebs cycle rates in spermatozoa of all germ cells for its single energy source of glucose or fructose . Recently published studies showed that the activities of the glycolytic pathway, HMP pathway, and TCA cycle enzymes were estimated in caput, corpus, and cauda segments of epididymis . So the significantly increased levels of citrate, malate, and nicotinamide in the epididymis indicated reproductive energy metabolic disorders upon exposure to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…23 Recently published studies showed that the activities of the glycolytic pathway, HMP pathway, and TCA cycle enzymes were estimated in caput, corpus, and cauda segments of epididymis. 24 So the significantly increased levels of citrate, malate, and nicotinamide in the epididymis indicated reproductive energy metabolic disorders upon exposure to heat stress. Furthermore, the increased levels of malate and aspartate (Asp) suggest there would be alteration of the malate-aspartate shuttle in ATP generation in spermatozoa due to the effect of heat stress.…”
Section: Energy Metabolismmentioning
confidence: 99%
“…This may be due to the fact that less precursors are coming for the normal functioning of TCA cycle as supported by the disturbed glycolytic cycle (Kaur and Guraya -1981a) and lipid metabolism (Kaur and Guraya -1982) of the testis after treatment with alpha chlorohydrin. This may be due to the fact that less precursors are coming for the normal functioning of TCA cycle as supported by the disturbed glycolytic cycle (Kaur and Guraya -1981a) and lipid metabolism (Kaur and Guraya -1982) of the testis after treatment with alpha chlorohydrin.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased activities of ICDH, SDH and MDH in the interstitial tissue, Sertoli cells, spermatogonia, spermatocytes, spermatids and spermatozoa, which occur after treatment with alpha chlorohydrin suggests that the rate of their tricarboxylic acid cycle (TCA cycle) is slowed down. This may be due to the fact that less precursors are coming for the normal functioning of TCA cycle as supported by the disturbed glycolytic cycle (Kaur and Guraya -1981a) and lipid metabolism (Kaur and Guraya -1982) of the testis after treatment with alpha chlorohydrin. GDH is the key enzyme in the amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%